Smart Robot Uv Sebagai Sterilisasi Lantai Masjid Pencegahan Penularan New Variants Covid-19 Berbasis Internet Of Things - Muhammad Akil; Adil Awal; Fachrain Azis (APIC, 2023)
The design of the UV Smart Robot aims to produce alternative technology that can keep the mosque floor sterile as a solution to prevent the transmission of the corona virus 19 amid the emergence of new variants. This robot is able to maintain the cleanliness and sterility of the floor which is equipped with a type C ultraviolet lamp based on the internet of things, so that this robot can work automatically and can be monitored in real time. The research method we use is Research and Development (R&D) research that aims to produce or develop certain products. This method is applied to research procedures into 3 namely needs analysis, user needs analysis, product analysis. There are 3 tests carried out in the smart robot design, namely, remote control and ESP32 testing, camera testing and sterilization. As well as mathematical testing by conducting literature studies related to the level of effectiveness of UV rays used in robots. In testing the remote control and ESP32 runs according to the commands given to the robot. Then in camera testing which was carried out three times the experiment showed the location well. Furthermore, the mathematically sterilization of the SARS-CoV-2 virus requires 5 mj2 doses to be eradicated, so that through the use of an ultraviolet C oesram lamp with a dose of 10.48 J/m3 the eradication process can be carried out effectively. So it can be said that Smart Robot UV is able to be a solution to the spread of the emergence of new variants of covid-19, especially in houses of worship in mosques that are congregants and become an application of appropriate technology.